MANAJEMEN SUMBER DAYA MANUSIA: IMLEMENTASI DALAM PENDIDIKAN ISLAM - M Nazar Almasri (Kutubkhanah, 2016)
Mangement of human resource represent one of area from public management covering palnning facet, organization, execution and ooperation. Human resource assumed imprortand progressively its role in target attainment, hence various experience and result of in the field of human resource collected sytematically in what referred as with the human resource management. Human resource exploiting, is process of leader activity meaning to employ the officer giving achievement enough and do not empoly the officer which no advantage, some effort in improving human resource of Islamic education: (a) Improving contruction of religion teacher with the common teacher from elementary storey level until college, (b) Setling competitor construction educated to in order to become the godfearing and religious human being to god which is single the most and also active sharing religion education for growth of science and technology, and (c) Higher education of religion develop the erudite mind in orde to comprehending and involving and also to translate the religion teaching of according to and in harmony with society life